GE_GERICHTE P/20522/2020 vom 14. November 2021 - GE Cour de justice (2021)
TENTATIVE(DROIT PÉNAL);VOL(DROIT PÉNAL);RÉVOCATION DU SURSIS;EXPULSION(DROIT PÉNAL);IN DUBIO PRO REO;ACQUITTEMENT | CP.139.al1; CP.22; CP.46.al1; CP.66a